Pengaruh Manajemen Ketatausahaan Terhadap Layanan Pendidikan - Ramadhan , Laila Najilatur; Safitri, Nadya (Program Studi Akuntansi IKOPIN, 2022)
This study aims to see whether Administrative Management in an institution has an effect on the performance of administrative services in an agency. The research approach is qualitative (case study), data sources, data collection techniques through interviews and observations. From this research, it can be concluded: (1) The quality of education cannot be separated from the role of administrative staff. (2) The development of competence and competence of staff is very much needed to improve the performance of administration in administrative services. (3) Evaluation of administrative performance is carried out to measure staff competence. (4) The ability of staff to manage the system in administrative management.